Pekerja Anak dalam Produksi Pertanian: Menilai Kembali Batasan Pekerjaan Anak Melalui Maqasid al-Syariah di Negara Bagian Kwara, Nigeria - Abolaji, Abdulraheem Taofeeq (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Kwara State, Nigeria, where agriculture remains the primary source of livelihood, continues to experience widespread child labour due to weak enforcement of labour regulations and persistent household poverty. Children's involvement in agricultural production frequently exceeds acceptable forms of work, exposing them to risks that threaten their health, education, and overall development. This study reassesses the limits of children's work in agricultural production through the perspective of Maqasid al-Shariah by examining whether existing practices are compatible with the Islamic objectives of child protection. This study employed a qualitative research design combining doctrinal analysis of Islamic legal sources with empirical field research. Primary data were collected through in-depth interviews and focus group discussions involving farmers, parents, children, and Islamic scholars in Kwara State. The data were analyzed thematically using the analytical framework of Maqasid al-Shariah. The findings reveal that child labour in agricultural production is primarily driven by poverty, limited access to education, and cultural norms that normalize children's economic participation. Although Islam recognizes the educational value of age-appropriate work and family responsibility, children's involvement in hazardous agricultural activities that interfere with education and endanger their physical and psychological well-being is inconsistent with the objectives of Maqasid al-Shariah, particularly the protection of life, intellect, lineage, and human dignity. The study further finds that the concept of maturity in Islamic law should not be interpreted as a justification for exploitative child labour. Reassessing the limits of children's work requires integrating labour regulations with the principles of Maqasid al-Shariah to establish a balanced framework that protects children's rights, prevents exploitation, and promotes sustainable human development in Kwara State, Nigeria.